The Arabidopsis thylakoid transporter PHT4;1 influences phosphate availability for ATP synthesis and plant growth. (3rd September 2015) - Karlsson, Patrik M.; Herdean, Andrei; Adolfsson, Lisa; Beebo, Azeez; Nziengui, Hugues; Irigoyen, Sonia; Ünnep, Renáta; Zsiros, Ottó; Nagy, Gergely; Garab, Győző; Aronsson, Henrik; Versaw, Wayne K.; et al.
Summary The Arabidopsis phosphate transporter PHT4;1 was previously localized to the chloroplast thylakoid membrane. Here we investigated the physiological consequences of the absence of PHT4;1 for photosynthesis and plant growth. In standard growth conditions, two independent Arabidopsis knockout mutant lines displayed significantly reduced leaf size and biomass but normal phosphorus content. When mutants were grown in high‐phosphate conditions, the leaf phosphorus levels increased and the growth phenotype was suppressed. Photosynthetic measurements indicated that in the absence of PHT4;1 stromal phosphate was reduced to levels that limited ATP synthase activity. This resulted in reduced CO2 fixation and accumulation of soluble sugars, limiting plant growth. The mutants also displayed faster induction of non‐photochemical quenching than the wild type, in line with the increased contribution of ΔpH to the proton‐motive force across thylakoids. Small‐angle neutron scattering showed a smaller lamellar repeat distance, whereas circular dichroism spectroscopy indicated a perturbed long‐range order of photosystem II (PSII) complexes in the mutant thylakoids. The absence of PHT4;1 did not alter the PSII repair cycle, as indicated by wild‐type levels of phosphorylation of PSII proteins, inactivation and D1 protein degradation. Interestingly, the expression of genes for several thylakoid proteins was downregulated in the mutants, but the relative levels of the corresponding proteins were either not affected or could not be discerned. Based on these data, we propose that PHT4;1 plays an important role in chloroplast phosphate compartmentation and ATP synthesis, which affect plant growth. It also maintains the ionic environment of thylakoids, which affects the macro‐organization of complexes and induction of photoprotective mechanisms.